Reducing microbial contamination on historical leather artifacts at the Auschwitz-Birkenau State Museum using ethanol in the form of mist - Kraśnicki, Krzysztof; Pydyn, Natalia; Papis, Aleksandra; Guzińska, Krystyna; Kaźmierczak, Dorota; Maciołek, Urszula; Wawrzyk, Anna (Frontiers in Microbiology, 2025)
PurposeThe aim of the study was to evaluate the biocidal efficacy and determine the influence of 90% ethyl alcohol applied in the form of a mist on the surface of model and historical leather.Materials and methodsThe main object of the study were historical leather shoes from the collections of the Auschwitz-Birkenau State Museum (A-BSM) in Oświęcim (Poland). Microorganisms found before on historical leather objects in A-BSM were inoculated onto samples of model and historical leather. Ethanol mist was applied with an airbrush with optimized parameters for 15 s at a concentration of 90%. To increase the biocidal effectiveness, the samples were sealed in a tight package and stored for 22 hours. The effect of disinfection was assessed using culture-dependent methods. Changes on the surfaces was assessed using SEM, FTIR, and XPS techniques.ResultsOn surfaces inoculated with microorganisms in the following quantities: 105 − 108 CFU bacteria and 105 CFU fungi, a reduction of 99.51% to 99.99% was observed. Ethanol disinfection had no negative effect on the surface morphology and collagen structure.ConclusionsDisinfection with ethanol applied in the form of mist can be effectively used to eliminate microbiological contamination of historical objects made of leather in A-BSM.